A realistic dynamic model for gear fault diagnosis. (February 2018) - Dadon, I.; Koren, N.; Klein, R.; Bortman, J.
Abstract: A reliable dynamic model that predicts the vibrations of a gear transmission containing a fault may allow us to recognize the effects of that fault, to identify its severity, and to develop methods for characterizing its type by using a limited number of experiments. In this research, a new generic model for gear dynamics is proposed. This model is solved numerically, and combines the most advanced approaches for gear modeling, including: modeling the contact between gear pairs as a set of springs, modeling the effect of faults on the mesh stiffness, and integrating the geometric errors. As a result, the model simulates successfully the acceleration signal of a realistic gear pair in a realistic environment. In this paper, we present a different approach to simulate partial tooth face faults, which takes into account the partial contact loss along the tooth contact line due to the fault's geometry. We propose a new analytical formulation for modeling complete tooth face faults that are located across the entire contact area. Additionally, a modified analytical expression for describing the tooth profile errors is proposed. Using a realistic simulation, we were able to experimentally validate the model. Highlights: A new generic model for gear dynamics is proposed. A different approach to simulate partial tooth face faults. A new analytical formulation for modeling complete tooth face faults. A modified analytical expression for describing the tooth profile errors. The model simulates successfully the acceleration signal of a realistic gear pair.